TINJAUAN YURIDIS TERHADAP PENERBITAN SERTIPIKAT PENGGANTI DI KANTOR PERTANAHAN KABUPATEN KLATEN MENURUT PP NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - ARIFIN, YUSUF (Dinamika Hukum, 2015)
The purpose of this research is to review and to analyze juridical toward the publishing of replacement certificate, and the benefits and the obstacles in the Land Affair Office on the District of Klaten according to Government Regulation Number 24 year 1997 about land registration. Background, with the passage of time on land ownership rights holders on land certificates, often problems on the owned certificate occur even though land certificate is a strong evidence of the ownership rights to land. Those problems for example is destruction of certificate of land rights, the certificate is lost, caused by carelessness and confusion in finding a replacement certificate so that the land affair office is the authorized agency in processing those certificates. Keyword : The Publishing of replacement certificate, Goverment Regulation Number 24 Year 1997.